Sirosis Hepatis - Reversibel atau Irreversibel? - Bernard Jonathan Christian Yong; Marco Vidor (Cermin Dunia Kedokteran, 2022)
Sirosis hepatis adalah tahap akhir penyakit hati dengan berbagai penyebab, antara lain kelainan  metabolik atau infeksi hepatitis B dan hepatitis C. Hingga saat ini, sirosis hepatis diyakini sebagai proses tidak reversibel, yang berujung dengan transplantasi hati. Namun, seiring dengan perkembangan teknologi dan pemahaman tentang patogenesis, sirosis hepatis mungkin bersifat reversibel. Liver cirrhosis is a final stage of liver disease with many etiologies, i.e. metabolic disorder or infection like type B hepatitis and type C hepatitis. Liver cirrhosis is still being considered as an irreversible disease, which leads to liver transplantation. But as far as the development of technology and knowledge of liver cirrhosis pathogenesis, liver cirrhosis might be considered as a reversible process.